REPRESENTASI PERSPEKTIF CITRA NEGATIF MASYARAKAT TERHADAP INSTITUSI POLISI DALAM FILM ATHENA KARYA ROMAIN GAVRAS - Ahsanal Alpha Riyadil Jinan (2024)
Athena is a French film directed by Romain Gavras and has been on Netflix since September 2, 2022. This movie tells about the different perspectives of three brothers who live in an immigrant complex in the suburbs of Paris in responding to the murder case committed by a police officer against his younger brother. This research aims to see how the perception of the perspective of the negative image of the community towards the police institution in the Athena movie through John Fiske's semiotic approach which is constructed into three stages divided into the level of reality, the level of representation, and the level of ideology. In this study, researchers used a descriptive qualitative analysis method with John Fiske's theory of the codes of television, to find out the scenes related to the negative image perspective. The results of this study show that the representation of the negative image perspective of the community towards the police can occur due to conflicts that arise among the community according to the conflict theory proposed by Ralf Dahrendorf. The researcher concludes that the six scenes selected can be said to be relevant at this time because social conflicts that occur between community groups and members of the police can lead to a negative image perspective of the community towards the police institution itself.